Vzťah náboženstva a umenia v literatúre svetovej a slovenskej moderny - Bátorová, Mária (Slavia Occidentalis, 2016)
The study analyzes the relation between religion and art in the world, and in Slovak modernist literature. It also examines religion and art from the point of view of its scholarly reception in the context of European literature. It builds on the division of artists of religious orientation based on Bernhard Rang’s two types: a) Claudelian and b) Green-ian. A part of the study provides new insights into Slovak literary modernism. Despite the expectation that modernism would exclude Christian works of literature, the opposite happened: modernism tested Christian works of art and emphasized their ability to capture the subtle aspects of human existence. In this way, a weakness of modernism was exposed: its degenerative function when it focuses only on material aspects. A historical overview has shown that Slovak intellectuals were used to living in an alternative cultural environment and nurturing an alternative culture. This experience proved useful to them in the 20th century, particularly after 1945. During communist rule, the underground church played a major role in Poland and in Slovakia. In Slovakia, Catholic dissidents were of great importance to the developments that led to the Velvet Revolution in November 1989.